MAPPING BRITTLE FRACTURE ZONES IN THREE DIMENSIONS: HIGH RESOLUTION TRAVELTIME SEISMIC TOMOGRAPHY IN A GRANITIC PLUTON - Marti D.; Carbonell R.; Tryggvason A.; Escuder J.; Perez-Estaun A. (My University, 2002)
Fractured and altered zones within a granitic pluton are mapped in three dimensions by means of high resolution seismic traveltime tomography. The input traveltimes were picked from offset and azimuth variable vertical seismic profiles (OVSP) acquired in three boreholes and from seismic shot gathers of four CDP high resolution seismic reflection profiles recorded on the surface. For the OVSP data a hydrophone streamer placed in the boreholes recorded the acoustic energy generated (a signal with a frequency content between 15 to 150 Hz) by a Vibroseis truck at source points distributed every 30 m in a rectangular grid of 620 m by 150 m. The combination of borehole and surface seismic data resulted in an increase in the ray density of the shallow subsurface. The tomographic algorithm uses a variable model grid, with a finer grid spacing close to the surface were ray density is highest and the velocity variations are strongest. Therefore the resulting velocity models feature more detail at shallow levels. A simple and smooth starting velocity model was derived from P -wave velocity logs. Careful surface geological mapping, and borehole geophysical data, P - and S -wave velocity logs and Poisson's ratio depth functions, provided key constraints for a physically reasonable 3-D interpretation of the tomograms. The low velocity anomalies constrained by the tomographic images were interpreted as unconsolidated rock, fractures and altered zones which correlate with structures mapped at the surface or velocity anomalies identified in the logs. Subsequent resolution analysis revealed that the derived velocity model is well constrained to depths of 60 m.
Keywords: FRACTURES; SEISMIC TOMOGRAPHY; SEISMIC VELOCITIES